Improving the Quality of Early Childhood Education Institutions Based on Integrated Educators and Facilities for Teachers and Children: A Literature Review - ritayulia ubbg; rahmattullah; sariakin (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This research delves into the enhancement of quality in Early Childhood Education (ECE) institutions, focusing specifically on the integration of skilled educators and the provision of adequate facilities for both teachers and children. Recognizing that the early years of a child's life are critical for cognitive, emotional, and social development, this study emphasizes the urgent need for high-quality educational environments. A comprehensive literature review is conducted to synthesize existing research on the components that constitute quality in ECE, including the qualifications and training of educators, the design and maintenance of educational facilities, and the role of parental and community involvement. The review highlights various models of successful ECE programs worldwide, assessing factors such as curriculum design, teacher-child ratios, classroom management, and resource availability. It also investigates the significance of professional development opportunities for educators, emphasizing how continuous learning and support can greatly improve teaching practices. Furthermore, the research explores the relationship between physical environments—such as safe outdoor play areas, age-appropriate learning materials, and accessibility—and their impact on children's engagement and learning outcomes. Through this analysis, the study identifies best practices and innovative strategies that can be adopted to create more synergistic and supportive educational settings. The implications of this research are directed towards policymakers, educational leaders, and stakeholders as they work toward improving ECE standards and ensuring that young learners receive the quality education they deserve. By fostering a culture of collaboration among educators, parents, and the community, it is possible to enhance the overall educational experience for children and support their holistic development.